Optimasi Efektivitas Mesin Vacuum Foarming Sebagai Dasar Penentuan Prioritas Perbaikan Menggunakan Overall Equipment Effectiveness (OEE) - Reynaldy Eka Saputra Wisnu Wardana; Herlina Herlina (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
PT. XYZ is a manufacturing company engaged in plastic packaging processing. The research problem is the high level of machine downtime that affects production output and the achievement of company targets. The data used in this study were downtime data from August 2025 to January 2026. Overall Equipment Effectiveness (OEE) was used to measure availability, performance, and quality, while Mean Time Between Failure (MTBF) and Mean Time To Repair (MTTR) were applied to analyze machine reliability. Pareto diagrams and Failure Mode and Effect Analysis (FMEA) were used to identify the main causes of downtime and determine maintenance priorities. The results of this study are expected to support more effective maintenance strategies and improve production efficiency.